EFFECT OF H2O2 AND MnO2 AS OXIDATORS OF GOLD AND COPPER LEACH PROCESSES FROM PRINTED CIRCUIT BOARDS - Yudha Pratesa; Aji Wibisono; Wahyuaji Narottama Putra; Yunita Sadeli; A. Zakiyuddin; Sri Harjanto (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
In general, electronic waste management in the form 2 of printed circuit boards (printed circuit boards/PCBs) is carried out by the process of removing components and taking precious metals that are easily recycled. However, in Indonesia, the recycling process for extracting precious metals has not been much processed, even though they contain precious metals such as copper and gold. This research was conducted to find a more economical and environmentally friendly treatment process by using an oxidizer of Hydrogen Peroxide (H2O2) and Manganese Oxide (MnO2) and reducing the level of HCl used. Observation of metal leaching results using Atomic Adsroption Spectroscopy (AAS) showed the value of recovery (recovery) of gold and copper reached 59.1% and 59.8% for 0.5M HCl + 2.5% H2O2. However, the recovery value of copper has reached its optimum point at the addition of 1.5% H2O2. The use of 3% & 5% MnO2 results in recovery values of 12% and 24% for gold and copper. Observation of the cross section shows the dissolution of the copper metal from the PCB and accompanied by a change in the color of the solution from clear to green, the more concentrated the more the amount of dissolved copper metal shows the characteristic of CuCl solution. The results of the comparison of the two types of oxidizers show that H2O2 is better than MnO2 in producing higher Cu and Au metals more than 3 times.